Gaining insight into actual and preferred sources of coaching knowledge - Erickson, K.; Bruner, M. W.; MacDonald, D. J.; Côté, J. (International Journal of Sports Science and Coaching, 2008)
Previous research has suggested that current formal coach education programs do not fully meet the learning needs of coaches. The purpose of the present study was to examine actual and preferred sources of coaching knowledge for developmental-level coaches. Structured quantitative interviews were conducted with coaches (N = 44) from a variety of sports. Learning by doing, interaction with coaching peers, and formal coach education were the top actual sources of coaching knowledge. Discrepancies were found between actual and preferred usage of learning by doing, formal coach education, and mentoring. Coaches indicated they would prefer more guided learning and less self-directed learning by doing. Further, differences in preferred sources were identified between coaches wishing to move to an elite level versus coaches wishing to stay at a developmental level. Findings highlight the importance of both experiential and formally guided sources of coaching knowledge and the context-specific nature of coach learning.